A Seismic Geotechnical Hazard Study in the Ancient City of Noto (Italy). (2016) - Castelli, Francesco; Cavallaro, Antonio; Ferraro, Antonio; Grasso, Salvatore; Lentini, Valentina
Abstract: South-Eastern Sicily has been affected in past times by several destroying earthquakes with high values of estimated magnitude. The aim of the seismic hazard microzonation studies performed at the City of Noto is to quantify the spatial variability of the site response on some typical historical scenario earthquakes that would be expected in the area. In order to quantify the expected ground motion, the manner in which the seismic signal is propagating through the subsurface has been defined. Propagation is particularly affected by the local geology and by the geotechnical dynamic ground conditions of the studied area. The data largely consist of the stratigraphic profiles obtained by in situ tests i.e. borings, MASW tests, Down-Hole tests, SDMT tests; some are accompanied by static and dynamic laboratory tests, such as Resonant Column, monotonic compression loading Triaxial tests and Direct shear tests. Processing of all these data allowed the ground response analysis at the surface, in terms of time history and response spectra, of some areas of the city using the linear-equivalent codes EERA, STRATA and DEEPSOIL, useful for microzonation of seismic geotechnical hazards.